사회적환경이 청소년비행에 미치는 영향 -위험요인과 보호요인을 중심으로 - 정혜원; Hye Won Jung (청소년복지연구, 2008)
This research is focused on, at first, whether inquiring the risk and the protective factors separately from delinquency of Korean adolescences are valid or not. Also, the research is concentrated on whether the protective factors can control the risk factors, which influence delinquency. The 2003 Korea Youth Panel Survey data were used for analysis and the total number of subjects were 3, 449 adolescents. Data were analyzed using factor analysis, logistic regression and hierarchic moderated regression analysis, analysis of variance. As the result of the study, first, parent supervision, parent attachment, and teacher attachment are the inhibiting factors; therefore, delinquent friends and wrong parenting are valid to be referred as the factors that cause delinquency. However, among the protective factors, parent attachment and grades cannot be confirmed as the direct causes of delinquency. Second, it is revealed that the protective factors can soothe the delinquency, which are from the risk factors.